A primer on stroke prevention and treatment : an overview based on AHA/ASA guidelines - Goldstein, Larry B. (Wiley-Blackwell, 2009)
Society-sanctioned guidelines are valuable tools, but accessing key information can be a daunting task. This book illuminates a clear path to successful application of the American Heart Association/American Stroke Association guidelines. Organized for fast reference, this new volume helps practitioners improve patient care.